Theoretical Study of Addition Reaction (4-3) of Some Derivatives of N,N-Dimethyl Amino Methylene ketone with Methanesulfonyl Chloride Using Level of theory M062X/6-31g(d) - Mosa, Yasser (Latakia University Journal -Basic Sciences Series, 2018)
The Addition (4-1) reactions of some derivatives of N,N-dimethy amino methylene ketone with methane sulfonyl chloride have been studied using one of methods of density functional theory (DFT): M062X with 6-31g(d) bases set. The thermodynamic and kinetic properties of reactions have been estimated. The results showed that the addition reactions are preceding spontaneously in gas phase at room temperature.